Keanekaragaman jenis laba-laba di Kawasan Hutan Mangrove Tongke-tongke Sinjai Timur Kabupaten Sinjai Sulawesi Selatan - Mayangsari, Tirta; Hasyimuddin, Hasyimuddin; Sijid, St. Aisyah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Spiders belong to the phylum Arthropoda, class Arachnida, and order Araneae. Spiders can serve as indicators of ecosystem disturbances. This study aims to identify the morphological characteristics, web models, and species diversity of spiders in the Mangrove Forest Area of Tongke-tongke, East Sinjai, Sinjai Regency, South Sulawesi. The research was conducted using an exploratory method at four stations: the tourist station, the rehabilitation station, the station near the ponds, and the station near the settlements. The results showed five species of spiders: Nephila kuhlii, Gasteracantha cancriformis, Argiope appensa, Argiope catenulata, and Lycosa sp. Each spider species found has different morphological characteristics. The web models found are generally circular, and some have stabilimenta. The diversity index values categorized as low were found at the tourist station, the rehabilitation station, and the station near the settlements, while the station near the ponds had a medium diversity index. The evenness index categorized as high was found at the station near the ponds, the rehabilitation station, and the station near the settlements, while the tourist station had a medium evenness index. The dominance index showed that three stations had medium dominance indices, namely the tourist station, the rehabilitation station, and the station near the settlements, while the station near the ponds had a low dominance index. These findings highlight the importance of monitoring and conserving spider diversity to maintain the stability of the mangrove ecosystem.